Benchmarking the Stability of State-of-the-Art H2O2 Electrocatalysts under Acidic Conditions - Fortunato, Guilherme V.; Jung, Daniele C.; Lourenço, Julio C.; Bhuyan, Pallabi; Choi, Ji Sik; You, Xiangyu; Lim, Sumin; Melchionna, Michele; Sezen, Hikmet; Hofmann, Jan P.; Fornasiero, Paolo; Lanza, Marcos R.V.; et al. (ACS Catalysis, 2025)
Electrocatalytic hydrogen peroxide (H2O2) production presents a promising alternative to conventional synthesis methods, such as the anthraquinone process. It utilizes electrocatalysts to selectively reduce oxygen through a two-electron transfer (ORR-2e-) mechanism. However, designing affordable, selective, and stable catalytic materials is challenging, as they face degradation under reaction conditions. To evaluate the long-term performance and reliability of electrocatalysts, accelerated stress tests (ASTs) are commonly employed to simulate and understand the catalyst’s degradation pathways in a shorter time. For the electrosynthesis of H2O2, however, a standardized approach is notably absent, and there is a dearth of comparative analysis across various catalyst classes. In this study, we have designed and tested three distinct AST protocols to investigate the deactivation processes involved during the electrocatalytic H2O2 production in acidic media. We assessed the performance of four leading catalysts, each exhibiting over 90% selectivity. These included palladium single atoms, gold and palladium nanoparticles, and cobalt nanoparticles encapsulated in carbon, all supported on high surface area carbon. Our investigation revealed substantial variations in stability, contingent upon the specific material and the applied degradation protocol. This approach enables a comprehensive understanding and evaluation of the stability of electrocatalysts as well as facilitates the development of more continuous and cost-effective H2O2 production routes.
CRIS-Team Scopus Importer:2025-05-23
Keywords: accelerated stress tests; catalyst degradation; electrocatalytic stability; hydrogen peroxide production; oxygen-reduction; real-time dissolution monitoring